Second IVIg course in Guillain‐Barré syndrome patients with poor prognosis (SID‐GBS trial): Protocol for a double‐blind randomized, placebo‐controlled clinical trial. Issue 4 (24th September 2018) - Walgaard, Christa; Jacobs, Bart C.; Lingsma, Hester F.; Steyerberg, Ewout W.; Cornblath, David R.; van Doorn, Pieter A.; ,
Abstract : One course of intravenous immunoglobulins (IVIg) of 2 g/kg is standard treatment in Guillain‐Barré syndrome (GBS) patients unable to walk independently. Despite treatment some patients recover poorly, in part related to rapid consumption of IVIg, indicating that they may benefit from a second course of IVIg. The aim of the study is to determine whether a second course of IVIg, administered 1 week after start of the first course in patients with GBS and predicted poor outcome improves functional outcome on the GBS disability scale after 4 weeks. Secondary outcome measures include adverse events (AEs), Medical Research Council sumscore and GBS disability score after 8, 12, and 26 weeks, length of hospital and ICU admission, mortality, and changes in serum IgG levels. GBS patients of 12 years and older with a poor prognosis, based on the modified Erasmus GBS outcome score (mEGOS) at 1 week after start of the first IVIg course are eligible for randomization in this double‐blind, placebo‐controlled (IVIg or albumin) clinical trial. This study will determine if a second course of IVIg administered in the acute phase of the disease is safe, feasible, and effective in patients with GBS and a poor prognosis. This Dutch trial is registered prospectively as NTR 2224 in the Netherlands National Trial Register (NTR) which is the Primary Registry in the WHO Registry Network for the Netherlands.